Demographic and economic trends: implications for international mobility - Martin, Philip (Munich, 2009)
"About three percent of the world's 6.1 billion people were international migrants in 2000. Population growth is expected to slow between 2000 and 2050 in comparison to 1950-2000, but international migration is expected to rise as persisting demographic and economic inequalities that motivate migration interact with revolutions in communications and transportation that enable people to cross borders. The default policy option to manage what is sometimes deemed out-of-control migration, adjusting the rights of migrants, is unsatisfactory, prompting this review of longer term factors affecting migration patterns, including aging in industrial countries, rural-urban migration that spills over national borders, and the migration infrastructure of agents and networks that moves people. The paper concludes with an assessment of the likely effects of the 2008-09 recession on international migration."